L'Academie de Lausanne entre humanisme et réforme (ca. 1537-1560) - Crousaz, Karine (Education and society in the Middle Ages and Renaissance ;, 2012)
The Lausanne Academy was the first Protestant Academy in a French-speaking territory, created twenty years before the one in Geneva. In the 1540's, the Lausanne Academy developed a new model for higher education that influenced the entire Calvinist world. Far from forming only pastors, it attracted the sons of Swiss and European Protestant elites through its advanced trilingual education (Latin, Greek, and Hebrew), in accordance with the cultural standards developed by Renaissance humanism. This book, based on a vast body of unpublished archival sources, examines the Lausanne Academy's historical development, academic program, students, faculty, and finances, revealing it as an essential milestone in the history of European education where the blossoming of humanistic culture and confessional rivalries met.